Amplification of tumor oxidative stresses by Poly(disulfide acetal) for multidrug resistance reversal. (September 2021) - Zong, Qingyu; Wang, Kewei; Xiao, Xuan; Jiang, Maolin; Li, Jisi; Yuan, Youyong; Wang, Jun
Abstract: Discovering new strategies to overcome multidrug resistance (MDR) is still urgently needed. MDR is associated with the overexpression of transmembrane efflux pumps, and adenosine triphosphate (ATP) is indispensable for its function. Herein, we developed a pH- and glutathione (GSH)-responsive amphiphilic poly(disulfide acetal) (PCS) containing cinnamaldehyde (CA) and disulfide groups that amplify oxidative stress for anticancer drug delivery and simultaneously overcome drug resistance in cancer cells. Reactive oxygen species (ROS)-generating CA and the disulfide groups to deplete GSH and synergize to amplify oxidative stress in cancer cells by oxidizing nicotinamide adenine dinucleotide with hydrogen (NADH) to nicotinamide adenine dinucleotide (NAD + ). The production of ATP is preferentially inhibited, leading to the malfunction of efflux pumps due to the lack of ATP and making resistant cells more impressionable to anticancer drugs. The in vitro and in vivo experiments confirmed that PCS could induce amplified oxidative stress and efficiently overcome MDR in cancer cells. We believe that the polymer with amplified oxidative stress in cancer cells holds great promise in developing polymer-based drug delivery systems to reverse MDR for cancer therapy. Graphical abstract: Image 1